Systemic reviews: Financing of higher education internationalisation - Ti Liu; Aminuddin Hassan; Mohd Ashraff Bin Mohd Anuar (Perspectives in Education, 2023)
The global higher education landscape has witnessed an increasing trend towards internationalisation in recent years; hence the demand for funding such endeavours has grown significantly. However, funding internationalisation efforts can be a challenging task for institutions. This review discusses various funding models for higher education internationalisation and the challenges posed by insufficient funding. This will be followed by a discussion on the following models:  government funding, private philanthropy, corporate sponsorship, and partnerships with foreign universities, the role of tuition fees in funding internationalisation, and the challenges posed. Ultimately, this paper will propose a framework for funding that is based on an analysis of successful internationalisation strategies from around the world and intends to guide various funding bodies on how to best allocate resources for this purpose. By implementing this framework, countries shall overcome financial constraints that limit the extent to which internationalisation can be pursued, while also ensuring that the benefits of such efforts are shared equitably across their populations. This paper also explores the challenges facing the higher education internationalisation and the hurdles present in the funding process. A successful example in China has been studied thoroughly. This paper argues that while there is no one-size-fits-all approach to funding internationalisation efforts, a diversified funding approach that leverages various funding models can help institutions overcome funding challenges and achieve their internationalisation goals.